Nolong.in: an android based incident notification application with push notification technology - Arthur Bachtiar Gunawan; Seng Hansun; Marcel Bonar Kristanda (Institute of Advanced Engineering and Science, 2019)
In driving, the most important thing to be considered is safety. The incident problem can happen anytime and anywhere without anyone knowing it before, especially in Cikarang where the level of incident is quite high. It is very important for the public community to act and respond quickly at the time on and around the occurring incident. Nolong.in application is an exact solution because it can send real time notifications to its users. This response is meant to assist individuals who have been using Nolong.in to help other users who need urgent help when the time of incident in order to prevent unwanted situations. In this research, push notification method has been implemented by using Firebase Cloud Messaging (FCM). The result of the research is the notification click ratio is 90.91% and the click time is 1 minute and 27 seconds. Based on the questionnaires’ results given to the community conclude that Nolong.in application is very beneficial for Gojek Cikarang community's safety.